Analisis Penerapan Code Splitting Library React pada Aplikasi Penjualan Mebel Berbasis Website - Daniel Tanudjaja; Radius Tanone (Maranatha University Press, 2021)
Mebel Murah is a shop that sells furniture products located in Semarang, Central Java, Indonesia. Due to Covid-19, the sales revenue have decreased due to limited access for buyers. Therefore, an innovation is needed to overcome this, namely by creating a website that can support especially the marketing and sales of furniture products to the public. The aims of this research is to focus on testing the rendering speed of components through the React Profiler to analyze the comparison of component rendering times on the client side of the code breaking features of the React library. The result of this research is to produce a website by utilizing the code splitting feature to display information content related to products sold by Mebel Murah stores.